Atiological prevalence of Nipple Discharge (The Planet, 2022)
Background: Nipple discharge is a common symptom in clinical practice. It is the third most common symptom after breast pain and lump. The risk of malignancy is higher when discharge unilateral, spontaneous bloody or serous. Objectives: The objective of this study is to find out the cause of nipple discharge and its relation to the breast cancer. Methods & Material: Patient present with nipple discharge about 85 cases selected from outpatient and indoor patient department of Mugda Medical College & Hospital from July 2019 to December 2020. Women age between 18 to 50 years present with nipple discharge without clinically palpable lump. All patient with nipple discharge evaluated by Triple assessment such as History, Clinical Examinations, USG, Mammography, Cytology and Histopathological examination and hormonal status of TSH and prolactin level. Results: These case series showed bilateral nipple discharge of 70 cases were mechanical stimulation, 1 year after cessation of lactation, hypothyroidism, hyperprolactinemia and fibrocystic disease. Rest 15 cases had unilateral nipple discharge were papilloma, duct ectasia and 1 case found duct cell carcinoma in situ (DCI). Conclusion: Benign breast lesions are the most common cause of nipple discharge. Breast cancer is rare.  We must be assessed the patient step wise and exclude malignancy.
Keywords: Nipple discharge; Ultrasonography; Mammography; Histopathology